Pengaruh Pencucian Membran Ultrafiltrasi Menggunakan Surfactan Dan NaOH Pada Proses Penyaringan Air Terproduksi - Sonny Wijaya; Syarfi Daud; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of water treatment technology that can be used for treat produced water is membrane technology. The most of challenging in membrane technology is fouling. The objective of this research are to study influence of ultrafiltration membrane washing to flux recovery and removal resistance by using surfactant and NaOH for treat produced water. Membrane that to be used on this research is membrane ultrafiltration with pore size between 0.1500 until 0.0014 micron and using capillary module configuration. The method that to be used is current-cross flow for filtration proses with filtration time 180 minutes with pressure in 0.2 bar, 0.4 bar, 0.6 bar and concentration of cleaning agent surfactant and NaOH in 1.5%, 2.0% and 2.5% by using counter-cross flow with pressure 0.8 bar and time for washing in 30 minutes. The highest washing effectiveness rate of 69.53% obtained by using surfactant 2.5% and filtration pressure 0.6 bar, the highest leaching efficiency based on flux recovery value is 99.32% and 99.65% for removal resistance obtained by using surfactant 2.5% and filtration pressure 0.2 bar.  Key words: flux recovery, fouling, produced water, removal resistance, surfactant, ultrafiltration membrane